Instagram Halal Cosmetics Reviews: Emotion Polarity and Presentation Modality Effects on Information Quality and Purchase Intention - Susilowati, Fitriah Dwi; Ridlwan, Ahmad Ajib; Fikriyah, Khusnul; Timur, Yan Putra (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This study investigates the relationship between Instagram evaluations of halal cosmetics and Perceived Information Quality. This study also investigates how Perceived Information Quality influences the purchase of halal cosmetics. This quantitative study uses an experimental design to give 180 respondents a five-scale questionnaire with two emotional polarity and modality modifications. Neutral-mix internet reviews of halal cosmetics had a greater impact on information quality. Instagram halal cosmetics purchasing intention is positively correlated with perceived information quality. This study suggests that halal cosmetics marketers might utilize rich modalities like audio and moving visuals for Instagram marketing. They can also boost good and negative consumer reviews that explain the product.